Konsep Integrasi Sains dan Agama Perspektif Al-Attas: Relevansinya dalam Menanggulangi Dekadensi Moral Generasi Z - Muhammad Sholeh Afif; Imron Rossidy (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to elucidate Syed Muhammad Naquib al-Attas’s concept of integrating science and religion and to analyse its relevance in addressing the moral decadence of Generation Z in Indonesia in the digital era. This study employed a qualitative approach using a descriptive library research method. The findings affirm that al-Attas’s integration is not an additive incorporation of religious values into modern science, but a radical Islamization of contemporary knowledge through the deconstruction of Western secular elements and reconstruction based on the Islamic worldview, with ta’dīb as the core process in forming the adab-oriented person (insān adabī). This framework proves highly relevant and urgent in countering the loss of adab among Generation Z, manifested in high rates of psychological distress, depression, promiscuity, and loss of shame due to exposure to secular and hedonistic information. Implementing ta’dīb-based Islamic education can equip Generation Z with a robust Islamic worldview filter, enabling them to direct technological proficiency toward ma‘rifatullāh and divine pleasure, while becoming a Muslim generation that is mentally resilient and morally noble.   Keywords: Generation Z, integration of science and religion, Moral Decadence, Syed Muhammad Naquib al-Attas, ta’dīb